Defining the Ideal Patient with Hepatocellular Carcinoma for Second-Line Treatment. (19th June 2020) - Roviello, Giandomenico; Casadei-Gardini, Andrea; Nobili, Stefania; Mini, Enrico; Fancelli, Sara
Abstract : Background . Second line of treatment of hepatocellular carcinoma (HCC) has notably changed in recent years as three novel drugs with a different mechanism of action have demonstrated to improve survival compared to placebo; thus, there is a need to better define the profile of optimal candidates to second-line treatment with these drugs in order to maximize clinical benefit. Materials and Methods . We performed a pooled analysis from the subgroup analysis of all published phase III trials for approved targeted therapy in the second line of treatment for HCC, with the aim to discover possible clinical-pathological predictive factors. Results . Four studies were included in the analysis for a total of 2137 cases whose results supported the use of these novel agents in male patients with ECOG: 0, extrahepatic metastases, and HBV infection. Conclusions . Future studies are awaited to define best candidates for novel agents approved in the second line of treatment for HCC.